Девятный Спас: [роман] / Анатолий Брусникин - Брусникин Анатолий (АСТ, 2008)
Экземпляры: РБАБ (20190304) / Инвентарный номер: 47745 / Цена: 240.00 / Авт.знак: Б 89 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6